Edukasi Etika Bisnis Untuk Pelaku Usaha Mikro Kecil Menengah (Umkm) - Istianingsih , Robertus Suraji (Jurnal Abdimas Ekonomi dan Bisnis, 2022)
The purpose of this activity is that Business Ethics Education participants understand the importance of applying ethical principles in doing business, Business Ethics Education participants are willing to participate in the socialization of understanding the application of ethical principles in business and Business Ethics Education participants understand the application of ethical principles in business. The implementation method used is by way of lectures, discussions and tutorials on practical questions via Teleconference with the Online Meeting Application. The material provided includes a discussion of (1) the role of ethics in business for MSME actors, (2) Benefits in doing business for MSME actors and (3) Application of ethical principles in business for MSME actors. Keywords: Business Ethics Education, Micro, Small and Medium Enterprises (MSMEs). Keyword : Business Ethics Education, MSMEs, Online Education